Fair Cop : Learning the Art of Policing - Chan, Janet B. L. (Janet Bick Lai), 1948- (Book collections on Project MUSE., 2003)
Publisher's description: Police forces everywhere have been undergoing major social and organizational changes. In this, one of the few longitudinal studies of police socialization, Janet Chan, Christopher Devery, and Sally Doran present the complexity of police socialization under these changing conditions. Following 150 new police recruits through two years of training and apprenticeship, the authors question the traditional model of socialization that assumes a degree of stability and homogeneity in the organizational culture. They suggest that recruits' developmental paths can be much more varied and police culture is increasingly vulnerable to change. Drawing on interviews, observations, and questionnaires, the authors depict the complex processes by which recruits adapt, redefine, cope with, and make sense of the positive and negative aspects of their training and apprenticeship. Bringing together rigorous quantitative analyses with rich ethnographic description, Fair Cop provides new empirical data and theoretical understanding about the reproduction and change of police culture.